POLA BAGI HASIL, HARGA PRODUKSI, DAN DISTRIBUSI LABA: PERSPEKTIF POLITICAL ECONOMY OF ACCOUNTING (STUDI PETANI GARAM DI KARANGANYAR) - Muhammad Alfaroby; Bambang Haryadi (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
One of the problems of the salt production business in Karanganyar is someone who owns land The main problem of the prolonged salt business is the problem of persistently low prices below the cost of production. Until now, the chaotic price of salt has not been overcome by the government. Farmers as helpless parties find it difficult to overcome these problems, especially farmers who work the land alone with the Cooperation system. This research aims to assess the cooperation of salt business profit sharing carried out in Karanganyar Village, Sumenep Regency. The research method used is qualitative with a critical analysis paradigm from the perspective of the Political Economy of Accounting (PEA). The results showed that the pattern of profit sharing is fully determined by landowners because they have the power, the shift in the profit sharing system from paron to tellon is very detrimental to farmers because they have to bear very high production prices, in all situations the price of profit distribution (profit) with this pattern has destroyed the hopes of farmers, salt imports are the main cause of the slump in people's salt prices, smart collectors take advantage of the situation by becoming the power to determine the price of salt, there is a practice of cheating collectors by reducing the weight of farmers' scales,to increase salt production, farmers are forced to borrow capital to buy geomembrane to collectors with the consequence of being obliged to sell at low prices.